Cooling crystallizer design for potash alum - Wan, Chee Yuen (2010)
The objectives of this project were to study the theoretical and experimental aspects of cooling crystallization, to design and implement a batch cooling crystallizer for potash alum in water solution using relatively low-cost laboratory equipment and to optimize the experimental procedure to allow for reliable and reproducible data collection. Literature review was carried out on industrial crystallization and the importance of crystallization kinetics. A batch cooling crystallizer was designed and a set of experimental procedures for data collection and analysis was implemented. These were achieved using relatively low-cost equipment such as the WQC-24 Water Quality Meter to measure conductivity and the optical microscope to measure particle size distribution. Experimental techniques and operating conditions of the crystallizer were optimized to produce reliable and reproducible results from 2 batch experiments. Limitations to this experiment setup and procedure include the sensitivity of the equipment used to impurities and noise, and that this procedure can only be used for compounds that impart charge when dissolved in solution. Future improvements include repeated tests to further confirm reproducibility and experimental determination of metastable zone width of potash alum in water solution to optimize yield and performance of the crystallizer.